Modelling of high‐power hybrid DC circuit breaker for grid‐level studies. Issue 2 (1st February 2016) - Lin, Weixing; Jovcic, Dragan; Nguefeu, Samuel; Saad, Hani
Abstract : The modelling principles for hybrid DC circuit breakers (CBs) which is developed to support DC grid protection studies and transient studies involving DC protection are studied. The coordinated control and interlocking of the four subunits (two semiconductor valves and two mechanical switches) are analysed. The model represents accurately the opening sequence, closing sequence and a modified model which includes DC fault current limiting mode (for short duration). The CB self‐protection and driver‐level valve protection are included in the model. Unidirectional DC CB and bidirectional DC CB are presented. Simulations on EMTP‐RV are used to verify the proposed models. The key operating conditions are tested, such as: opening the DC CB under fault current, malfunction of upper layer protection system, re‐closing a DC CB under rated DC current, re‐closing a DC CB to DC fault and current limiting (for short duration) control of the DC CB.